1988
DOI: 10.1111/j.1365-2133.1988.tb01779.x
|View full text |Cite
|
Sign up to set email alerts
|

Active participation of eosinophils in patch test reactions to inhalant allergens in patients with atopic dermatitis

Abstract: Intracutaneous testing and patch tests with house dust mite and grass pollen allergens were performed in patients with atopic dermatitis. Only patients with an immediate type skin reaction to house dust mite or grass pollen allergens showed a positive patch test reaction to these allergens 24-48 h after testing. Occasionally positive patch test reactions at 20 min, 2 h and 6 h were also observed. Patch test reactions were not found in normal controls or atopic patients without atopic dermatitis. Analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(112 citation statements)
references
References 18 publications
5
105
0
2
Order By: Relevance
“…tions could be induced by patch tests with environmental allergens (house-dust tnites, grass pollen) as a tnodel for this tnode of triggering AD (3,4,11,31), In these patients, as in LPRs, a significant infiltration of eosinophils in the skin was detected within 2-6 h. By means of monoclonal antibodies against eosinophil toxic proteins, it was shown that these eosinophils were preactivated and that most of their granule content was released into the surrounding tissue. Twenty-four hours after allergen challenge, eosinophils could be detected even in the epidermis.…”
Section: Eosinophils In Atopic Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…tions could be induced by patch tests with environmental allergens (house-dust tnites, grass pollen) as a tnodel for this tnode of triggering AD (3,4,11,31), In these patients, as in LPRs, a significant infiltration of eosinophils in the skin was detected within 2-6 h. By means of monoclonal antibodies against eosinophil toxic proteins, it was shown that these eosinophils were preactivated and that most of their granule content was released into the surrounding tissue. Twenty-four hours after allergen challenge, eosinophils could be detected even in the epidermis.…”
Section: Eosinophils In Atopic Dermatitismentioning
confidence: 99%
“…As demonstrated by several groups in a number of patients, environmental allergens, e.g. those of grass pollen and house-dust mites, induce eczematous reactions when applied to the skin (4,11,31). Moreover, it was shown that skin contact with these allergens may result in a general exacerbation of AD (1,5,17,26,36).…”
mentioning
confidence: 99%
“…It has been speculated that immediately after PT some allergens penetrate the epidermis, bind the IgE molecules on mast cells in the dermis and induce an immediate type reaction. Mast cell release eosinophil chemotactic factors and some of the infiltrating eosinophils become activated [41]. As already discussed, recent studies demonstrated that in the skin lesions of AD patients' Der pl-specific T clones are Th2 lymphocytes expressing IL-4 and IL-5 and no IFN-α (42).…”
Section: The Role Of Inhalant Allergensmentioning
confidence: 85%
“…Bruijnzeel-Koomen et al showed 70% positive PT response, applying house dust mite and pollen allergens on the back of AD adult patients, previously removing the superficial stratum corneum by consecutive application of adhesive tape [41]. No positive responses were found in atopic patients without AD or in controls.…”
Section: The Role Of Inhalant Allergensmentioning
confidence: 99%
“…Increased serum levels of MBP (97) and ECP (98), and deposits of MBP in lesional skin (74) occur in patients with AD. Moreover, cutaneous eosinophils are present in positive patch tests with specific aero-allergens in AD patients (99). The role of the eosinophils in AD is, however, unknown.…”
Section: Eosinophil-derived Toxic Proteinsmentioning
confidence: 99%